The Relationship between Hardiness Personality and Husband's Social Support with Mother's Parenting Stress in Dealing with Children's Disruptive Behavior - Oki Mutiara Asparfa Dewi; Siswanto; Erna Agustina Yudiati (Nusantara Science and Technology Proceedings, 2023)
Maternal parenting stress can occur because mothers are the main caregivers who will face daily problems, especially those who have children with disruptive behavior. The purpose of this study was to determine the relationship between a hardiness personality and a husband's social support with a mother's parenting stress in dealing with children's disruptive behavior simultaneously or partially. Using a quantitative approach with the number of participants as many as 61 mothers who have preschool-age children (3-5 years old), have gone to PAUD (KB or TK) in Semarang City, and the child has disruptive behavior. Participants were selected through the accidental sampling method and data analysis using multiple regression analysis. The results showed that there was a very significant simultaneous relationship between hardiness personality and husband's social support with mothers' parenting stress in dealing with children's disruptive behavior, with an effect of 32.0%. There is a negative and very significant relationship between hardiness personality and parenting stress of mothers in dealing with children's disruptive behavior with an effect of 19.4%. When dealing with children's destructive behavior, there was a positive and significant relationship between the husband's social support and the mother's parenting stress, with an effect of 12.6%. This study aims to demonstrate that maternal resilience is an important factor in reducing or suppressing maternal parenting stress when dealing with children's disruptive behavior. A limitation of this study is that the scale is extended using Google Forms, so researchers cannot see participants' reactions when they provide information to complete the scale in Google Forms. A suggestion for future researchers is to conduct a broader study on mothers' parenting stress in different cases, such as children's use of gadgets and devices.